PENGUJIAN TEORI FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL REPORTING (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - Helda F. Bawekes; Aaron M. A. Simanjuntak; Sylvia Christina Daat (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
The purpose of this research is to examine the effect of fraud pentagon theory in explaining phenomenon of fraudulent financial reporting at Indonesian companies in the year period of 2011 to 2015. This research uses 9 (nine) independent variables to achieve this objective, namely:Financial targets, Financial stability, External pressure, Institutional ownership, Ineffective monitoring, External audit quality, Changes in auditors, Change of directors, and Frequent number of CEO's picture. The dependent variable was used is fraudulent financial reporting that proxied by restatement. This research uses 210 samples from 42 companies listed on Indonesia Stock Exchange in the year between 2011 and 2015. This research had done by conduncting a quantitative method with secondary data. This secondary data was taken from the financial statements, which are downloaded from the company's website and the Indonesia Stock Exchange web. Method of determining the sample in this research were using purposive sampling. And logistic regression method was used as a data analysis tool. The result of this research proves that financial stability and frequent number of CEO's picture have significant effect to the fraudulent financial reporting. However, financial targets, external pressure, institutional ownership,ineffective monitoring, external audit quality, changes in auditors and directors change have no significant effect on the fraudulent financial reporting